Adsorption and Detection of Toxic Gases on CuO-Modified SnS Monolayers: A DFT Study - Xinyue Liang; Ping Wang; Kai Zheng; Xuan Yang; Meidan Luo; Jiaying Wang; Yujuan He; Jiabing Yu; Xianping Chen (Sensors)
The emission of toxic gases such as NO2, NO, SO2, and CO from industrial activities, transportation, and energy production poses significant threats to the environment and public health. Traditional gas sensors often lack high sensitivity and selectivity. To address this, our study uses first-principles density functional theory (DFT) to investigate CuO-SnS monolayers for improved gas sensor performance. The results show that CuO modification significantly enhances the adsorption capacity and selectivity of SnS monolayers for NO2 and NO, with adsorption energies of −2.301 eV and −2.142 eV, respectively. Furthermore, CuO modification is insensitive to CO2 adsorption, demonstrating excellent selectivity. Structural and electronic analyses reveal that CuO modification reduces the band gap of SnS monolayers from 1.465 eV to 0.635 eV, improving the electrical conductivity and electron transfer, thereby enhancing the gas adsorption sensitivity. Further analyses highlight significant electronic interactions and charge transfer mechanisms between CuO-SnS monolayers and NO2 and SO2 molecules, indicating strong orbital hybridization. In conclusion, this study provides a theoretical basis for developing high-performance gas sensors, showing that CuO-SnS monolayers have great potential for detecting toxic gases.